Corruption in Vietnamese Higher Education - McCornac, Dennis (International Higher Education, 2008)
There is no doubt that the Vietnamese higher education system is in need of serious reform. Corruption is epidemic, and actions must be taken to change the environment in which these practices flourish. The recent decision by the Ministry of Education and Training to adopt new, stricter measures on national exams and the increased media attention on corruption are steps in the right direction. If Vietnam desires to obtain an international standard educational system, required reforms are necessary from all parties. Perhaps, most importantly, there must be a monumental change in the attitude and thinking by students, faculty, and parents. Education is a right and privilege that is earned, not a commodity to be sold by administrators and faculty.